Penerapan Penggunaan Irah-Irah “Demi Keadilan Berdasarkan Ketuhanan Yang Maha Esa” dalam Konteks Pencapaian Keadilan - Samuel Saut Martua Samosir (Universitas Islam Balitar, Blitar, 2019)
It is required that every head of the verdict has specific nomenclature “On behalf of Justice in the name of one and only God” which entrenched in Article 197 paragraph 1of the Criminal Code Procedure. The head of the verdict stressed that there is a word of justice based on the one and only God which has the main purpose is for the court examination in order to pursue justice, but there is a problem when the contents of the ruling did not provide justice for the prosecuted party, it can be indicated that the case filed to the appeal court by parties whose refuse the decision. According to the legal issues there exist the new paradigm to the concept of the head of the verdict which states“On behalf of Justice in the name of one and only God” only for decisions that have permanent legal force, this is an effort to achieve procedural justice and moral Justice